Representasi Pesan Moral Dalam Film Imperfect The Series : (Analisis Semiotika Roland Barthes) - Rovida Femila Sari, Nur; Hakim, Lukman (IAIN Madura, 2023)
Discussions about films as a tool to convey messages are indispensable in public entertainment. With the development of the film world, Web series has recently become the talk of the community. One of the most popular is the series